Brote de miocarditis - Mendiondo Tapia, Belkis; Más, Pedro; Agramonte, Servando; Ortega, Bruno; Pedroso, Luis; de Armas, Graciano; Torrens, Rafael (Revista Cubana de Pediatría, 2023)
Presenta el estudio de 10 casos diagnosticados de miocarditis a virus.